2014 IEEE International Conference on Robotics and Automation (ICRA) 2014
DOI: 10.1109/icra.2014.6907396
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis for long-term robotic mapping

Abstract: Abstract-This paper presents a new approach to mobile robot mapping in long-term scenarios. So far, the environment models used in mobile robotics have been tailored to capture static scenes and dealt with the environment changes by means of 'memory decay'. While these models keep up with slowly changing environments, their utilization in dynamic, real world environments is difficult.The representation proposed in this paper models the environment's spatio-temporal dynamics by its frequency spectrum. The spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 61 publications
(78 citation statements)
references
References 18 publications
0
78
0
Order By: Relevance
“…Sünderhauf and Neubert [34,35] mined a dictionary of superpixel-based visual-terms from long-term data and used this dictionary to translate between the appearance of given locations across seasons. Krajnik et al [36] used Fourier analysis to identify the cyclical changes of the environment states and showed that predicting these states for a particular time improves long-term localization [37].…”
Section: Visual Navigation In Changing Environmentsmentioning
confidence: 99%
“…Sünderhauf and Neubert [34,35] mined a dictionary of superpixel-based visual-terms from long-term data and used this dictionary to translate between the appearance of given locations across seasons. Krajnik et al [36] used Fourier analysis to identify the cyclical changes of the environment states and showed that predicting these states for a particular time improves long-term localization [37].…”
Section: Visual Navigation In Changing Environmentsmentioning
confidence: 99%
“…We modified the way to obtain l coefficients in [5] to tackle the aforementioned problem by extracting multi-periodic patterns. To obtain a Fourier spectrum of the raw data, we find a frequency ω k with the highest absolute value, then subtract it from the data and transform it again.…”
Section: Spectral Representation In Fourier Transformmentioning
confidence: 99%
“…F (ω) = F T (λ). In [5], l coefficients with the highest absolute value along with their frequencies ω k (for k = 1, . .…”
Section: Spectral Representation In Fourier Transformmentioning
confidence: 99%
See 2 more Smart Citations